Conceptualización y diseño de un modelo para evaluar la gestión de información organizacional en el Banco de la República, como entidad de banca central en Colombia (2015)
In the present work of applied depth, the conceptualization and design of a model to evaluate the management of organizational information was carried out. Towards the realization of the project, the theoretical review on the topic of information management was developed, in order to establish the conceptual framework of the object of study and the relevance of the management to be evaluated. Based on the results obtained by the theoretical review, its design was carried out, based on an evaluation center, for the management evaluation, so that the proposed model starts from the analysis of the flows, the life cycle and the management programs . In its preparation, the pertinent analysis considerations were taken into account in order to establish the consistency and validity of the proposed standard.